Reconstruction of The Juvenile Criminal Justice System and The Giving of Diversion - Muhaimin Muhaimin (Jurnal Penelitian Hukum De Jure, 2021)
Children are not to be punished but to be given guidance and development, so that they grow and develop as completely normal, healthy and intelligent children. Sometimes children experience situations that make them commit illegal acts. Even so, children who break the law are not worthy of punishment, let alone put in prison. Law Number 11 Year 2012 concerning Juvenile Criminal Justice System demands a reorientation of the purpose of punishment which has an impact on the operation of the Juvenile Criminal Justice System. The formulation of the objectives of restorative justice and diversion mechanisms which are recognized as mechanisms for handling crimes committed by children demands that the performance of the criminal justice sub-system change its orientation. The problem of this research was how the construction and reconstruction of the giving of diversion are. This research used descriptive analysis method and normative juridical approach. Children are part of citizens who must be protected as a generation to continue the leadership of the Indonesian nation. The current ideal construction for children who are in conflict with the law applies the Law of Juvenile Justice System where children aged 7 years can be given diversion in the trial process. Article 21 of the Law of Juvenile Criminal Justice System and Government Regulation No. 65 Year 2015 concerning Guidelines for the Implementation of Diversion, children under 12 years of age who commit/are suspected of committing a criminal act shall then be returned to their parents and include them in education, coaching, and mentoring programs in government institutions or Social Welfare Organizing Institutions in institutions in charge of social welfare.